Run-On Sentence Errors in Indonesian Efl Learners’ Writing : Penelitian - Lintang Bidadari; Alya Syahlani Saragih; Andre Widianto; Rasid Saleh Matondang; Siti Ismahani (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
Writing is a complex skill for English as a Foreign Language (EFL) learners, particularly in terms of grammatical accuracy. One common grammatical problem found in students’ writing is the occurrence of run-on sentence errors, which reduce clarity and coherence. This study aimed to analyze the types of run-on sentence errors produced by Indonesian EFL learners and to examine how these errors can be reconstructed into well-formed English sentences. The study employed a qualitative descriptive research design involving eighthgrade junior high school students selected through purposive sampling. The data were collected from students’ handwritten descriptive paragraphs and analyzed by identifying run-on sentence errors, classifying them into types, and reconstructing the incorrect sentences using appropriate punctuation and coordinating conjunctions. The findings revealed two main types of run-on sentence errors: fused sentences and comma splices, with fused sentences occurring more frequently. The results indicate that learners experience difficulties in recognizing sentence boundaries and applying correct punctuation in English. The study suggests that explicit instruction focusing on sentence structure and clause relationships is essential to reduce run-on sentence errors in EFL writing.